THE EFFECT OF PREGNANCY YOGA ON THE SLEEP QUALITY OF PREGNANT WOMEN IN THE THIRD TRIMESTER AT THE MULYOASRI VILLAGE HEALTH CENTER - Meti Winarsih; Sulistiyah (Journal of Public Health Science, 2026)
During the third trimester of pregnancy, various physiological and psychological changes occur that can lead to poor sleep quality, such as back pain, increased nocturnal urination, and anxiety before childbirth. These conditions may negatively affect both maternal and fetal health if not properly managed. One of the recommended non-pharmacological interventions is prenatal yoga. This study aimed to determine the effect of prenatal yoga on sleep quality among third trimester pregnant women in the working area of Mulyoasri Village Auxiliary Health Center. This study used a quasi-experimental design with a Non-Equivalent Control Group Design. A total of 30 respondents were selected using purposive sampling and divided into two groups: 15 in the intervention group and 15 in the control group. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the Paired Sample t-test. The results showed that all respondents in the intervention group (100%) had poor sleep quality during the pretest. After receiving prenatal yoga intervention, 53.3% of respondents improved to good sleep quality. Statistical analysis showed a p-value of <0.001, indicating a significant effect. Meanwhile, the control group showed no significant change (p=0.670). In conclusion, prenatal yoga is an effective non-pharmacological intervention to improve sleep quality in third trimester pregnant women through both physiological and psychological relaxation mechanisms.